3D Printed Muon Detector Structures - SAM CRESSALL (2023)
The work presented in this thesis explores the feasibility of incorporating additive manufacturing (AM) solutions into the fabrication of structural components in cosmic-ray muon imaging (muography) systems. The work has been sponsored by Lynkeos Technology Limited (UK) who deploys muography to investigate nuclear waste containers. Currently, muography is in the early stage of industry adoption and offers advantages over traditional non-destructive testing (NDT) methods in safety, deployment, and material. This thesis has identified three challenges to realise the technology's commercial potential: timescales needed per image, design and assembly of the structure, and costs of materials and components. Lynkeos has previously collaborated with Swansea University to produce a proof of concept 3D printed structure which encases the required components. To address challenges, the system's fabrication, material, and assembly have been investigated and improved upon by applying a design process and accelerated lifecycle testing.The constraints, limitations and objectives of the system deigns have been summarised in a product design specification (PDS). Building on the PDS a novel design solution is proposed which improved upon previous design attempts by integrating electronics and incorporating modularity into the design. The novel design solution has demonstrated a detection area of 0.05m2, which is an increase of 335% over the previous design proposal. Additionally, the design was more compact than previous designs improving the portability. The novel design proved successful in measuring background radiation and locating a beta source emitter within the detection plane, demonstrating the feasibility of the modular design. Further conceptualised improvements leveraging AM design capabilities have decreased print time by 38% and material used by 36%, making the component more economically viable. The improvements also increase the probability of muon detection, reducing the time scale required for image reconstruction.The work then reviewed the radiation robustness of 3D printed parts. Accelerated lifetime testing was carried out to mimic the operating conditions of Lynkeos’ system. The first-ever characterisation of the response of Polyethylene Terephthalate Glycol (PETG) and Acrylonitrile Butadiene Styrene (ASA) to gamma radiation was carried out. The findings indicate that PETG exhibits excellent mechanical resistance to high-intensity gamma radiation. At an exposure of 0.75 MGy, PETG maintained 99.2% and 93% of its ultimate tensile strength and maximum strain, respectively. This exposure is over ten times the recommended dose the previously used material, polylactic acid, can withstand. These findings support Lynkeos’ manufacturing of cosmic-ray muon imaging structures and influence other industries hoping to leverage AM technologies in radioactive environments.